2018
DOI: 10.1038/s41467-018-07804-8
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Mycobacterium ulcerans cytochrome bc1:aa3 for the treatment of Buruli ulcer

Abstract: Mycobacterium ulcerans is the causative agent of Buruli ulcer, a neglected tropical skin disease that is most commonly found in children from West and Central Africa. Despite the severity of the infection, therapeutic options are limited to antibiotics with severe side effects. Here, we show that M. ulcerans is susceptible to the anti-tubercular drug Q203 and related compounds targeting the respiratory cytochrome bc1:aa3. While the cytochrome bc1:aa3 is the primary terminal oxidase in Mycobacterium tuberculosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
102
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(107 citation statements)
references
References 33 publications
5
102
0
Order By: Relevance
“…Same unfavorable result was obtained with selamectine used at a dose of 12mg/kg as proposed in previous publication [19]. However, it has been suggested that these two avermectin compounds might be used safely at higher doses [12], which could be evaluated in future studies. The dose of tedizolid TDZ used in the present study, 10 mg/kg, was shown to yield in mice pharmacokinetics close to that obtained in human at the therapeutic dose of 200mg [20-22].…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Same unfavorable result was obtained with selamectine used at a dose of 12mg/kg as proposed in previous publication [19]. However, it has been suggested that these two avermectin compounds might be used safely at higher doses [12], which could be evaluated in future studies. The dose of tedizolid TDZ used in the present study, 10 mg/kg, was shown to yield in mice pharmacokinetics close to that obtained in human at the therapeutic dose of 200mg [20-22].…”
Section: Discussionsupporting
confidence: 64%
“…The doses used in our experiment were drawn from available pharmacokinetic data. Ivermectine, a long lasting drug in human (half-life 15-19h) and in mice (9h) was shown when used in mice at a dose of 0.2mg/kg to yield serum concentration lower than that obtained in human at standard therapeutic dose [12]. We therefore used a higher dose (1 mg/kg) that, still, failed to control infection in our model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, M. ulcerans strains from Africa and Australia lack cytochrome bd and rely solely on the bc1-aa3 complex during respiration. Therefore, Q203 was found to be bactericidal against M. ulcerans (106). It is very possible that MAF L6 will be comparatively more susceptible to Q203 than MTB, given that the cytochrome bd rescue is also mutated in MAF L6.…”
Section: Resultsmentioning
confidence: 99%